1997
DOI: 10.1021/jp9716039
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Activation of Ammonia by Co+

Abstract: Mechanistic aspects of the reaction of Co + with ammonia are investigated by ab initio calculations. The potential energy surface is explored at the CASSCF level. Relative stabilities of the various stationary points on the reaction path are obtained by applying the CASPT2 technique. Binding energies for the reaction products CoNH 3 + , CoNH 2 + , and CoH + are calculated to be 52.1, 66.7, and 51.5 kcal/mol, respectively. They correspond reasonably well with the relevant experimental values of 58.8 ( 5, 61.3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…It was shown that the inclusion of dynamical correlation effects is very important to predict precisely the bond lengths between a metal and a ligand. 18,19 In most cases, the calculated results were in good agreement with the available experimental data.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…It was shown that the inclusion of dynamical correlation effects is very important to predict precisely the bond lengths between a metal and a ligand. 18,19 In most cases, the calculated results were in good agreement with the available experimental data.…”
Section: Introductionsupporting
confidence: 79%
“…[4][5][6][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Armentrout and co-workers [8][9][10][11][12] have carried out a series of experiments, using a guided ion beam mass spectrometry, to investigate the catalytic activity of the respective transition metal cations. They investigated activation processes of methane, 8 ammonia, 9 and water molecules 10,11 by the firstrow transition metal cations, and discussed the similarity and differences of the reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of Co ϩ with NH 3 has recently been studied by using MRMP, MR-SDCI, and CASPT2 methods. 45,46 In these studies, it was shown that MRMP and MR-SDCI give a similar result. 45 In this paper, we investigated the mechanism of the reactions of the first row transition metal cations (Sc ϩ , Ni ϩ , Cu ϩ ) with an ammonia molecule with the use of MRMP, MC-QDPT, MR-SDCI, and B3LYP methods.…”
Section: Introductionmentioning
confidence: 73%
“…31 Of course, these multireference methods require considerable computational costs, but recent progress has made it possible to apply those methods to molecular systems of moderate size routinely. [32][33][34][35][36] The number of theoretical studies on the reactions of the first-row transition metal ͑cation͒ plus elementary molecules is also growing, in which MR-SDCI, [37][38][39][40][41][42][43][44][45] MRMP ͑CASPT2͒, [45][46][47] or density-functional-theory ͑DFT͒ based methods [6][7][8][47][48][49][50][51][52][53] have been employed. Especially, there are increasing applications of the hybrid density functional B3LYP method, i.e., Becke's three parameter nonlocal hybrid exchange potential 54 with the nonlocal correlation functional of Lee, Yang, and Parr, 55 but its applicability to the transition state of the reaction has not been established yet ͑although it has been verified that B3LYP in most cases gives quite satisfactory results around the equilibrium struc-ture͒.…”
Section: Introductionmentioning
confidence: 99%
“…When reduced by CO to the metal cation and CO 2 , the metal oxide cation can serve as a mediator in the catalytic reduction of N 2 O by CO to N 2 and CO 2 [3,4]. The transition metal cations or transition metal oxide cations can provide fundamental information about catalytic action in different systems ranging from heterogeneous to homogeneous catalysis [5][6][7][8][9][10]. The reaction of oxygen transfer from N 2 O to CO can be catalysed by various transition metal cations in the gas phase and has been widely studied both experimentally and theoretically [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%